Tooth preparations: science & art. Author: Clovis Pagani, Co-workers: Eduardo Galera da Silva, Daniel Maranha da Rocha. Hanover Park, Illinois: Quintessence; 2017. ISBN: 978-1-78698-001-4. - Rodrigues, José Roberto (Brazilian Dental Science, 2017)
Tooth preparations: science & art AutorAuthorClovis Pagani - São Paulo State University (Unesp) - Institute of Science and Technology - Restorative Department  –  São José dos Campos - SP – Brazil.co-workers Eduardo Galera da Silva -   São Paulo State University (Unesp) - Institute of Science and Technology   -  Social and Pediatric Dentistry Department - São José dos Campos – SP – Brazil.Daniel Maranha da Rocha -    University of Sergipe -  Department of Dentistry of Lagarto- Lagarto - SE -  Brazil.Publisher: Quintessence Pub Co; 1 ed. (31 May 2017)Language: EnglishISBN: 978-1-78698-001-4.